Magnetic Bead Purification of Labeled DNA Fragments for High-Throughput Capillary Electrophoresis Sequencing. (June 2002) - Elkin, C.; Kapur, H.; Smith, T.; Humphries, D.; Pollard, M.; Hammon, N.; Hawkins, T.
We have developed an automated purification method for dye-terminator-based DNA sequencing products using a magnetic bead approach. This 384-well protocol generates sequence fragments that are essentially free of template DNA, salt, and excess dye-terminator products. In comparison with traditional ethanol precipitation protocols, this method uses no centrifugation, is rapid, completely automated, and increases the phred-20 read length by an average of 40 bases. To date, we have processed over 4 million samples with 94% averaging 641 phred-20 bases on the MegaBACE TM 1000 and 4000 and the ABI PRISM ® 3700 capillary instruments.